Distribution and biodegradation analysis of polyvinyl chloride microplastic by indigenous bacteria isolated from Supit Urang Landfill, Malang, Indonesia - KENNIS ROZANA; SITORESMI PRABANINGTYAS; DIMAS RICKO WIDYATAMA (Society for Indonesian Biodiversity, 2023)
Abstract. Rozana K, Prabaningtyas S, Widyatama DR. 2023. Distribution and biodegradation analysis of polyvinyl chloride microplastic by indigenous bacteria isolated from Supit Urang Landfill, Malang, Indonesia. Biodiversitas 24: 3853-3859. Microplastic waste is one of the most common forms of environmental pollution. Indonesia is the world's fourth largest contributor of plastic waste. One type of plastic that accumulates in the environment is Polyvinyl Chloride (PVC). Various attempts or methods have been developed to reduce PVC plastic waste, one of which is with the help of using indigenous bacteria. This research is essential in determining the best optimization method for PVC biodegradation agents through molecular and bioinformatic approaches. Indigenous bacteria were isolated from Supit Urang Landfill, Malang City, with three dilution levels (10-4, 10-5, and 10-6). The three highest isolates were taken for further biodegradation tests for 30 days and were identified based on the 16S rRNA gene. Then, the BLAST results were made into a phylogenetic tree to determine the kinship of each species. The isolation results obtained 17 bacterial isolates, selected by initial biodegradation screening for 10 days. Isolate K4 has a degradation percentage of 1.61±0.007379%. While isolates K4 and K15 have a biodegradation potential of 3.04±0.001861%. and 1.90±0.005576%. The BLAST results showed that K4 isolate had a 99% similarity to Staphylococcus capitis, K14 had a 99% similarity to Bacillus subtilis, and K15 had a 100% similarity to Acinetobacter pittii.